In Vivo Depletion of Dividing Donor Cells Using Post-Transplant Cyclophosphamide can Reduce the Development of Graft-Versus-Host Disease in a Humanised Mouse Model. (July 2018) - Adhikary, Sam; Geraghty, Nicholas; Alexander, Stephen; Sluyter, Ronald; Watson, Debbie
Abstract : Introduction: Graft-versus-host disease (GVHD) is a life-threatening complication of allogeneic bone marrow transplantation (BMT), a curative therapy for haematological malignancies. GVHD develops when donor immune cells in the graft become reactive against the host, damaging host tissues (liver, skin and gut). Depletion of dividing donor cells reduces GVHD severity in allogeneic mouse models, but there is limited data on the effects of depletion in humanised mouse models of GVHD. This study aimed to determine the effect of depleting dividing donor immune cells using post-transplant cyclophosphamide (PTCy) on the development of disease in a well-established humanised mouse model of GVHD. Materials and Methods: Isolated human peripheral blood mononuclear cells (hPBMCs) were injected (20 x 106 cells i.p) into NOD-SCID-IL2Rγnull (NSG) mice, with PTCy (33 mg/kg), or saline injected on days 3 and 4 post-hPBMC injection. Mice were monitored for 10 weeks for GVHD development using a clinical scoring system, with the engraftment of human immune cells checked by flow cytometry at 3 weeks (blood) and end-point (spleen). At end-point the relative expression of inflammatory cytokines in GVHD target organs were analysed by qPCR. Results: At 3 weeks post-hPBMC injection, similar percentages of human leukocytes were found in saline- (41.18 ± 5.58%) and PTCy-injected mice (31.27 ± 4.43%) (P = 0.198, n = 9 mice per treatment group), with the majority of these cells being T cells in both groups (Saline, 97.34 ± 0.91%; PTCy, 96.01 ± 0.84%) (P = 0.332). PTCy significantly increased the human CD4:CD8 T cell ratio compared to saline-injected mice (Saline, 0.7245 ± 0.07; PTCy, 1.633 ± 0.40) (P = 0.031). Furthermore, compared to saline, PTCy decreased the percentages of human CD4 + CD25 + CD127 lo regulatory T cells (Saline, 6.69 ± 0.64%; PTCy, 3.30 ± 0.52%) (P = 0.001) and human CD38 + CD8 + CD45RA - CCR7 - memory T cells (Saline, 81.46 ± 2.30%; PTCy, 64.62 ± 7.80%). PTCy reduced development of GVHD, with significantly reduced weight loss (P < 0.0001) and clinical score (P < 0.0001), and increased survival (MST = 52 days) compared to saline-injected mice (MST = 26 days) (P < 0.0001). Whilst both mouse groups demonstrated similar relative human IFNγ expression in the gut (P = 0.125) and liver (P = 0.162), PTCy significantly reduced relative human IL-17 expression in both tissues (P = 0.044 and 0.048, respectively). Discussion: This data indicates that the depletion of dividing donor cells using PTCy can reduce GVHD in this humanised mouse model, whilst allowing human cell engraftment. Further, PTCy reduces percentages of cells implicated in GVHD development. However, mice treated with PTCy still develop GVHD, so further strategies are required. Conclusion: This humanised mouse model of GVHD will allow investigation of combinatorial therapies that use depletion strategies targeting dividing human donor immune cells as potential GVHD therapeutics.